Very small planar broadband monopole antenna with hybrid trapezoidal–elliptical radiator. Issue 4 (27th February 2017) - Dastranj, Aliakbar
Abstract : A compact and broadband printed monopole antenna (PMA) with a hybrid trapezoidal–elliptical radiator is proposed. An overlap region between the trapezoidal and elliptical patches is introduced to enhance the impedance bandwidth. Meanwhile, by etching two symmetrical quarter‐elliptical slots on the ground plane and optimising the ellipticity ratio, further improvement in the impedance bandwidth is achieved. Measured results show that the antenna can cover the frequency range of 2.4–18.6 GHz (| S 11 | < −10 dB) while its total size is only 25 × 25 × 1.2 mm 3 . In addition, omnidirectional radiation patterns, desirable gain, high radiation efficiency and nearly constant group delay are obtained. Compared with recent PMAs, the proposed antenna has a smaller size and wider bandwidth, simultaneously.